Comparing the Spiritual Health and Quality of Life in Addicted and Non-Addicted Patients in the City of Birjand, Iran - Salmabadi, Mojtaba (Int J High Risk Behav Addict, 2016)
BACKGROUND: Substance abuse is a chronic phenomenon that affects many physical, psychological, social, familial and economic elements. Abusers are left with severely reduced interaction both with other individuals and society. OBJECTIVES: The aim of this study was to compare the spiritual health of addicts and people with a normal quality of life in the city of Birjand, Iran. PATIENTS AND METHODS: The sample consisted of 100 non-addicted subjects and 100 patients who were drug addicts in treatment centers and rehabilitation facilities both public and private in Birjand. Normal sampling measures were used to find subjects of the same age and gender. The subjects completed a spiritual health questionnaire and the short form of the world health organization’s (WHO) Quality of life questionnaire, and the data were analyzed using multivariate ANOVA. RESULTS: The results of ANOVA showed significant differences between addicted and non addicted individual on spiritual well-being subscales. CONCLUSIONS: The strengthening of spiritual and religious attitudes among drug users encourages them to engage in and justify actions that are relevant to their health. When this happens, their quality of life increases significantly.